Análisis del estado de la salud bucodental del departamento del Quindío del año 2022 (2024)
The knowledge about oral pathologies in the department of Quindío is limited, with the ASIS 2019 report being the most recent available. In this study, the oral health status of the Quindío population was analyzed for the year 2022, using a sociodemographic and epidemiological approach. 38,932 consultations for oral diseases registered in SISPRO Min Salud were collected and classified into 254 categories of the RIPS cubes. Using descriptive statistics and the professional Excel plus 2016 software, the information was organized in databases and the results were presented in bar and pie charts.